Co-construction of a data collection tool: A case study with Atikamekw women - Basile, Suzy; Hugo Asselin; Thibault Martin (ACME: An International Journal for Critical Geographies, 2017)
Dans les cultures Autochtones, les savoirs, les rôles et les pratiques étaient historiquement basés sur la réciprocité et la complémentarité entre les genres. En excluant les femmes Autochtones des processus de prise de décision, les politiques coloniales ont réduit la base de savoirs sur laquelle les décisions s'appuient. Les voix des femmes Autochtones ont longtemps été exclues des recherches et les chercheurs ont joué un rôle important dans leur marginalisation. C'est dans ce contexte -- et dans un effort de décolonisation de la recherche -- que nous présentons une étude de cas du processus de co-construction d'un outil de collecte de données avec des femmes Atikamekw. En préparant un projet de recherche sur le rôle des femmes Autochtones dans la gouvernance du territoire et des ressources naturelles, nous avons travaillé avec trois femmes Atikamekw, qui ont attribué une grande importance au processus d'obtention du consentement des participantes. Nous avons élaboré le formulaire de consentement ensemble, afin qu'il réponde à leurs préoccupations quant à la confiance, la transparence et l'implication de la communauté tout au long de la recherche. Décoloniser la recherche implique que les outils de collecte de données ne devraient pas être élaborés dans des bureaux universitaires, mais par une collaboration significative avec les participants à la recherche.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; femmes Atikamekw; projet charge mentale; périodes historiques; racisme; recherche participative; régions géographiques; sexisme; système colonial; systèmes d'oppressions

Boundaried caring and gendered emotion management in hospice work - Cain, Cindy L. (Gender, Work and Organization, 2017)
Caring work, which is premised on caring for and caring about recipients, involves a great deal of emotion management. Feeling rules shape expectations about emotion management and are informally shared through workers’ narratives about quality work. Using qualitative data from hospice workers in the southwestern US, I find that narratives of quality within hospice include emotion-management skills such as listening, truly caring, keeping calm and maintaining boundaries. Through an analysis of how workers discuss and map skills onto individual women and men co-workers, this article highlights two gendered patterns. First, even when women and men are thought to share high-quality skills, the ways these skills are described reinforce naturalistic understandings of gender. Second, men are seen to hold a broad range of emotion-management skills, but women are not described as holding the most important emotion-management skill: keeping boundaries. Understanding this differential application of emotion-management skills helps us to understand how gender and gender inequality are reproduced within caring work. © 2017 John Wiley & Sons Ltd
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; care; intersectionnalité; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; soins palliatifs; systèmes d'oppressions; thématiques; travail; travail du care; travailleureuses de la santé; émotions; états-unis

A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press ;, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."-- Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Girlhood interrupted: The erasure of Black girls' childhood - Epstein, Rebecca; Blake, Jamilia J.; González, Thalia (Georgetown Law, Center on Poverty and Inequality, 2017)
This groundbreaking study by the Georgetown Law Center on Poverty and Inequality provides—for the first time— data showing that adults view Black girls as less innocent and more adult-like than their white peers, especially in the age range of 5–14. The report builds on similar results that have emerged from studies of adult perceptions of Black boys. In 2014, for example, research by Professor Phillip Goff and colleagues revealed that beginning at the age of 10, Black boys are more likely than their white peers to be misperceived as older, viewed as guilty of suspected crimes, and face police violence if accused of a crime.1 SNAPSHOT OF THE DATA Compared to white girls of the same age, survey participants perceive that • Black girls need less nurturing • Black girls need less protection • Black girls need to be supported less • Black girls need to be comforted less • Black girls are more independent • Black girls know more about adult topics • Black girls know more about sex These results are profound, with far-reaching implications. Our findings reveal a potential contributing factor to the disproportionate rates of punitive treatment in the education and juvenile justice systems for Black girls.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; cours; discipline; droit; fem3300; filles noires; genre; identités LGBTQIA2+; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques; états-unis

THE COLOURED WOMEN’S CLUB OF MONTREAL, 1902-1940: African-Canadian women confronting anti-black racism - Este, David; Sato, Christa; McKenna, Darcy (Canadian Social Work Review, 2017)
À ce jour, il existe très peu d’écrits sur la contribution des personnes d’ascendance africaine à l’histoire de l’assistance sociale canadienne. À partir de sources secondaires et archivistiques, nous analysons la contribution du Club des femmes de couleur de Montréal (CFCM) au bien-être de la communauté noire de Montréal entre 1902 et 1940 du point de vue du racisme contre les Noir.e.s et du féminisme afro-canadien. Le CFCM a joué un rôle prépondérant dans ce bien-être en étant l’un des grands soutiens auprès des membres aux prises avec d’importantes difficultés dans une société où le racisme était omniprésent et où les perspectives d’avenir pour les hommes et les femmes étaient fortement limitées. Le club a organisé plusieurs activités qui ont permis aux membres de la communauté de survivre dans un milieu hostile aux personnes d’ascendance africaine. Il a ainsi été d’un grand secours et a favorisé un sentiment de communauté chez les Noir.e.s de Montréal. Nous avançons que, grâce aux efforts de ce club durant cette période, les Afro-Canadiennes sont d’abord devenues des actrices clés de la communauté et ensuite les premières intervenantes sociales. Il est impératif que les travailleurs sociaux reconnaissent la contribution des femmes engagées dans le CFCM afin de faire contrepoids aux récits historiques de notre profession qui proviennent surtout d’une culture hégémonique blanche.
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amériques; approches et analyses; canada; cours; fem3100; femmes* afro-descendantes; histoire et politique; militance; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Making space for Indigenous feminism - Green, Joyce A. (Fernwood Publishing, 2017)
The 2007 first edition of this book proposed that Indigenous feminism was a valid and indeed essential theoretical and activist position, and introduced a roster of important Indigenous feminist contributors. The book has been well received nationally and internationally. It has been deployed in Indigenous Studies, Law, Political Science, and Women and Gender Studies in universities and appears on a number of doctoral comprehensive exam reading lists. The second edition, Making More Space, builds on the success of its predecessor, but is not merely a reiteration of it. Some chapters from the first edition are largely revised. A majority of the chapters are new, written for the second edition by important new scholars and activists. The second edition is more confident and less diffident about making the case for Indigenous feminism and in deploying a feminist analysis. The chapters cover issues that are relevant to some of the most important issues facing Indigenous people--violence against women, recovery of Indigenous self-determination, racism, misogyny, and decolonisation. Specifically, new chapters deal with Indigenous resurgence, feminism amongst the Sami and in Aboriginal Australia, neoliberal restructuring in Oaxaca, Canada's settler racism and sexism, and missing and murdered Indigenous women in Canada."-- Résumé de l'éditeur.
Keywords: amériques; approches et analyses; australie; canada; cours; discipline; droits des femmes*; droits des personnes autochtones; féminisme autochtone; histoire et politique; justice sociale; mexique; militance; océanie; patriarcat; pol4105; premier cycle; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études décoloniales; études féministes

De la marge au centre : théorie féministe - hooks, bell (Cambourakis, 2017)
Avec "De la marge au centre", son deuxième essai paru aux États-Unis en 1984, bell hooks poursuit la réflexion initiée dans "Ne suis-je pas une femme?" Étudiant les succès et les manquements des mouvements féministes qui ont traversé le xxe siècle, elle constate l'échec de la création d'un féminisme de masse qui s'adresserait à toutes. Elle s'attache ainsi, dans un style toujours accessible, à bouleverser les représentations habituelles de la pensée féministe majoritaire en plaçant au centre de sa réflexion les femmes noires et/ou des milieux populaires, insistant sur le besoin profond d'une approche révolutionnaire de ces questionnements. Cet ouvrage percutant a imposé bell hooks comme l'une des voix les plus influentes et stimulantes de la scène féministe.
Keywords: 1900-1999; EDI; afro-féminisme; amériques; approches et analyses; black feminism; classe sociale; com5170; cours; discours dominant; fem1000; femmes* noires; féminismes noirs; histoire du féminisme; incontournable; justice sociale; militance; mouvements féministes; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; sex3383; sexisme; systèmes d'oppressions; thématiques; théorie féministe; états-unis

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

À l’intersection du genre et de l’origine nationale: quels sont les parcours professionnels des immigrants sélectionnés au Québec ? - Lacroix, Julie; Gagnon, Alain; Lortie, Vincent (Population, 2017)
Les différences d’insertion dans l’emploi entre immigrés et natifs sont étroitement liées à l’origine nationale et au genre. Alors que le désavantage des hommes immigrés non occidentaux est souvent expliqué en termes de discrimination et de transférabilité du capital humain, celui des femmes immigrées repose plutôt sur un argumentaire culturel, selon lequel la participation des femmes au marché du travail serait le reflet des rôles de genre dans la région d’origine. En utilisant les données d’enquête sur les travailleurs sélectionnés au Québec, nous examinons la rapidité avec laquelle les immigrés accèdent à l’emploi selon la nationalité et le genre. Ces derniers sont tous des requérants principaux de la catégorie des travailleurs qualifiés au Québec. Les facteurs liés aux « barrières culturelles », censés freiner l’accès des femmes à l’emploi, sont ainsi neutralisés dans l’analyse des différents groupes se destinant au marché du travail. Des modèles de Cox avec interactions montrent que l’effet de genre se juxtapose à celui de l’origine nationale des immigrés et révèlent des différences de genre pour l’accès au premier emploi, qui sont principalement modulées par les connaissances linguistiques. Au contraire, l’accès à un emploi conforme au niveau d’éducation diffère selon l’origine nationale, indépendamment du genre.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; antiracisme; approches et analyses; canada; cours; discipline; féminisme décolonial; premier cycle; périodes historiques; québec; racisme; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; systèmes d'oppressions; thématiques

Deer Woman: an anthology - LaPensée, Elizabeth; Alvitre, Weshoyot; Stonefish, Patty; Vasquez, Allie; Naragon, Rebecca; Thunder, Jonathan; Native Realities (Firm); Arming Sisters (Organization) (Native Realities, LLC, 2017)
Based on the true stories of Indigenous women throughout the world, Deer Woman: An Anthology is an extension of the Deer Woman: A Vignette, comic book that itself is a powerful expression and weaves the stories of Deer Woman into a modern narrative of the struggles of Indigenous women in North America. This anthology features the work of more than a dozen Native women sharing stories of survival, empowerment, and healing. Edited by Elizabeth LaPensée and Weshoyot Alvitre and featuring the work of: Patty Stonefish, Allie Vasquez, Mia Casesa, Darcie Little Badger, Tara Ogaick, Kimberly Robertson, Barbara Kenmille, Maria Wolf Lopez, Tatum Bowie, Jackie Fawn, Rebecca Roanhorse, Carolyn Dunn, Nashoba Dunn-Anderson, and more, this anthology is an important addition to the current conversation about violence against women, especially Native women.-from publisher's website.
Keywords: amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; bande-dessinée; care; cours; discipline; environnement; féminisme autochtone; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

Le positionnement intersectionnel comme pratique de recherche: faire avec les dynamiques de pouvoir entre femmes - Marcillat, Audrey; Miramond, Estelle; Rupert, Nouri; Çıngı Kocadost, Fatma (Les cahiers du CEDREF, 2017)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; cours; discipline; intersectionnalité; inégalités; militance; premier cycle; pédagogie; périodes historiques; régions géographiques; sciences humaines; sexisme; soc3113; sociologie; systèmes d'oppressions; thématiques; états-unis

Ce silence qui tue - O'Bomsawin, Kim (Wabanok, 2017)
Près de 1200 femmes autochtones assassinées ou disparues au Canada: c'est ce que la GRC affirmait dans un rapport en 2014. Déjà à l'époque, ce nombre était grandement sous-estimé. Aujourd'hui, la situation est encore plus alarmante. Pourquoi une femme autochtone est-elle plus à risque que n'importe quel autre citoyen canadien? Comment cette situation peut-elle perdurer dans un pays comme le Canada qui se veut un modèle en matière de droits humains? Travailleuses du sexe, victimes de violence familiale, militantes, proches d'une femme disparue ou assassinée, des femmes ainsi des hommes témoignent d'une réalité troublante et lancent un cri du cœur pour briser ce silence qui tue
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; cours; fem3200; femmes* et filles autochtones disparues et assassinées; premier cycle; périodes historiques; québec; racisme; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Femmes autochtones: la violence coloniale et ses avatars - Perreault, Julie (Relations, 2017)
Au Québec et au Canada, les femmes autochtones sont parmi les plus susceptibles d'être la cible de violences; une réalité qui met en lumière une histoire de colonialisme qui continue de faire des victimes.
Keywords: amériques; approches et analyses; canada; cours; discipline; femmes* autochtones; histoire et politique; intersectionnalité; militance; pol4105; premier cycle; québec; racisme; régions géographiques; science politique; science politique et droit; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; violences